The Verbal Systems of Aramaic - Bruweleit, Stefan, (Handbook of Oriental Studies. Section 1 The Near and Middle East ;, 2025)
In The Verbal Systems of Aramaic , Bruweleit analyses the Aramaic verbal systems from Old Aramaic to the modern dialects. He examines whether the verb forms are to be analysed as aspectual, temporal or modal and decides whether the verbal systems are to be regarded as aspect-, tense- or mood-prominent. On a diachronic level, the study investigates which conclusions the verbal systems allow regarding the classification and history of Aramaic. The work offers a hypothesis that explains the intricate use of the participle in Biblical Aramaic and shows that the North-Eastern Neo-Aramaic (NENA) dialects can be traced back to a common proto-dialect that split into at least four branches from which in turn the modern NENA dialects emerged.